Genome-Wide DNA Methylation Profiling in CD8 T-Cells and Gamma Delta T-Cells of Asian Indian Patients With Takayasu Arteritis - Kabeerdoss, Jayakanthan; Danda, Debashish; Goel, Ruchika; Mohan, Hindhumathi; Danda, Sumita; Scofield, R. Hal (Frontiers in Cell and Developmental Biology, 2022)
Background: Takayasu’s Arteritis (TA) is a chronic inflammatory disease that affects the aorta and its main branches at their origin. Genetic, pathological and functional studies have shown that CD8 and Gamma Delta (γ/δ) T- lymphocytes are involved in inflammatory processes in affected regions of arteries causing vascular damage. The molecular function of these lymphocytes remains unclear and currently no epigenetic studies are available in TA. We primarily performed genome wide methylation analysis in CD8 T cells and γδ T cells of patients with TA and compared with healthy controls. Methods: We recruited 12 subjects in each group, namely TA patient and healthy controls. Blood samples were collected after obtaining informed written consent. CD8 T cells and γδ T cells were separated from whole blood. DNA extracted from these cells and were subjected to bisulfite treatment. Finally, bisulfite treated DNA was loaded into an Infinium Methylation EPIC array. Bioinformatics analysis was used to identify differential methylation regions which were then mapped to genes. Results: Interleukin (IL)-32 and Lymphotoxin-A were genes significantly hypomethylated in CD8 T-cells. Anti-inflammatory cytokine genes, IL-10, IL-1RN and IL-27 were hypomethylated in γδ T cells of TA patients as compared to healthy controls. Gene enrichment analysis using Gene Ontology (GO) database and Kyoto Encyclopaedia of Genes and Genomes (KEGG) identified that genes involved in T-cell receptor signalling pathways were hypomethylated in CD8 T-cells and hypermethylated in γδ T cells of TA patients. Conclusion: CD8 T-cells might play a major role in immunopathogenesis of inflammation in TA, whereas γδ T cells may play a regulatory role.